Teori Tata Bahasa Generatif Transformatif Chomsky serta Aplikasinya dalam Gramatikal Bahasa Arab - Hum, Balkis Aminallah Nurul MIVTAKH (Journal of Arabic Language and Literature (ALLAIS), 2023)
This article aims to examine Chomsky's Transformative Generative language theory and its application in Arabic grammar. The method used in this study is qualitative based on literature study, which is a research method that provides an explanation by using analysis based on the literature that supports TGT studies. The research object of this study is Chomsky's language theory, namely Transformative Generative Grammar (TGT). This research answers two questions. First, "How is the explanation of Chomsky's generative transformative theory?". Second, "how is the generative transformative theory applied to Arabic grammar? The results of this study are that there are concepts used to understand TGT including: inner structure and outer structure (At-Tarokib As-Sathiyah and Tarokib Al-Asasiyah); competence and performance (Al Kifayatul Lughowiyah and Al-Adaaul Kalamiy); generative and transformative (At-Taulidiyah wa Tahwiliyah). Generative rules have forms like the rules found in standard writing. These rules include: Ruknun Fi'liyun consists of 1) fi'il + Ruknun Ismiy (Fa'il + Ma'ulun bih); 2) Ruknun Ismiy (Harf Jar + Alif Lam Ta'rif + Isim). While the Transformation Rules include: 1) Elimination (Harf, Isim, Fi'il, Amount); 2) Expansion; 3) Addition; 4) Change of Order; 5) replacement; 6) Abbreviation.